2017
DOI: 10.1007/s00240-017-0970-5
|View full text |Cite
|
Sign up to set email alerts
|

Stress–stones–stress–recurrent stones: a self-propagating cycle? Difficulties in solving this dichotomy

Abstract: Numerous studies have reported an association between stress and urolithiasis. Although urinary risk factors have been measured in several of these, compelling evidence of a causal relationship has not been established. A shortcoming is that alterations in single urinary parameters rather than ratios and quotients, which provide a more synergistic risk evaluation, have been measured. Recently, we speculated about a possible association between chronic stress and stone recurrence. This presents an intriguing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…17 However, in 2017 the same authors re-evaluated this data, using urinary marker ratios and quotients, and found no significant differences between the groups related to urinary risk factors. 20…”
Section: Discussionmentioning
confidence: 99%
“…17 However, in 2017 the same authors re-evaluated this data, using urinary marker ratios and quotients, and found no significant differences between the groups related to urinary risk factors. 20…”
Section: Discussionmentioning
confidence: 99%